Abuse liability, behavioral pharmacology, and physical-dependence potential of opioids in humans and laboratory animals: lessons from tramadol - Epstein, David H. (2006)
Assessment of abuse potential of opioid analgesics has a long history in both laboratory animals and humans. This article reviews the methods used in animals and in humans and then presents the data collected in the evaluation of tramadol, an atypical centrally acting opioid analgesic approved for marketing in the United States in 1998. Finally, data on the abuse of tramadol from postmarketing surveillance and case reports are presented. The consistency between animal and human study results and the predictive value of both are discussed. Overall, there was substantial agreement between animal and human data, with each having predictive value. Nonetheless, it is suggested that abuse-potential screening of new medications would benefit from an organized, integrated cross-species program.